Performance optimization of polymer electrolyte membrane fuel cells using the Nelder-Mead algorithm. (3rd August 2017) - Piela, Piotr; Mitzel, Jens; Gülzow, Erich; Hunger, Jürgen; Kabza, Alexander; Jörissen, Ludwig; Valle, Francesco; Pilenga, Alberto; Malkow, Thomas; Tsotridis, Georgios
Abstract: The direct-search simplex method for function optimization has been adapted to performance optimization of polymer electrolyte membrane fuel cells (PEMFCs). The established method is strongly application oriented and uses only experimentally determined data for optimization. It is not restricted to discrete parameters optimums and does not require the use of third-party software or computational resources. Hence, it is easy to implement in fuel cell testing stations. The optimization consists of finding, for a given fuel cell load, an optimum set of values of the 7 fuel cell operating parameters: the fuel cell temperature, the reactants' stoichiometric ratios, the reactants' inlet relative humidity, and the reactants' outlet pressures, resulting in the highest fuel cell performance. The performance is measured using a scalar function of the operating parameters and the load and can be defined according to needs. Two PEMFC performance functions: the fuel cell voltage and the system-related fuel cell efficiency were optimized using the procedure for practically sized PEMFC stacks of two designs. With respect to the nominal operating conditions defined as optimal for each stack design by its manufacturer, the gains from the optimization procedure were up to over 12% and up to over 7% for the stack voltage and efficiency, respectively. The validation of the procedure involved 5 stack specimens and four laboratories and consistent results were obtained. Highlights: A systematic method for finding optimum PEMFC operating conditions is introduced. The method is used to find conditions of maximum performance of PEMFC stacks. Improvements over 12% in stack voltage at a fixed load are shown. Improvements over 7% in system-related stack efficiency at a fixed load are shown.